2013
DOI: 10.1111/j.1600-0587.2013.07868.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of regional and local processes in structuring a larval trematode metacommunity of Helisoma trivolvis

Abstract: Metacommunity theory has advanced our understanding of how local and regional processes aff ect the structure of ecological communities. While parasites have largely been omitted from metacommunity research, parasite communities can provide the large sample sizes and discrete boundaries often required for evaluating metacommunity patterns. Here, we used assemblages of fl atworm parasites that infect freshwater snails ( Helisoma trivolvis ) to evaluate three questions: 1) what factors aff ect individual host in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 49 publications
4
52
2
Order By: Relevance
“…In a study of trematode richness and metacommunity structure within Helisoma trivolvis , Richgels et al (2013) found that the probability of infection in individual hosts associated strongly with snail body size, while trematode richness at the population level correlated negatively with pH and marginally positively with pond size. Our results supported the influential roles of host body size and pond area but also highlighted the effects of free-living richness and colonization opportunities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study of trematode richness and metacommunity structure within Helisoma trivolvis , Richgels et al (2013) found that the probability of infection in individual hosts associated strongly with snail body size, while trematode richness at the population level correlated negatively with pH and marginally positively with pond size. Our results supported the influential roles of host body size and pond area but also highlighted the effects of free-living richness and colonization opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…From May to August 2013, we collected snails from freshwater ponds Contra Costa, Alameda, and Santa Clara counties (Johnson et al 2013; Richgels et al 2013). We selected accessible pond ecosystems across grassland, oak woodland, and chaparral biomes to encompass a broad range in resource availability, community composition, surrounding habitat, and physical and spatial characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We collected snails ( Helisoma trivolvis and Physa acuta ) from ponds in the San Francisco Bay Area of California between May and August of 2013 and 2014 (see Richgels et al 2013 Fig. 1 for map).…”
Section: Methodsmentioning
confidence: 99%